RELATION BETWEEN PANCASILA AND ISLAMIC VALUES ON RELIGIOUS FREEDOM - Sulasman, Sulasman; Dewi, Eki Kania (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2014)
The discourse of religious harmony and freedom is still a current study and much studied through various approaches, including in the perspective of history, sociology, and culture. In Indonesia, normatively, the practices of religious harmony and freedom are referred to both Islamic religion and Pancasila values. The two normative references are positioned in line. Thus, even for the people, Pancasila has a spirit of Islam, because the framers of Pancasila (and Konstitution UUD 1945) are Moslem like Muhammad Yamin and Sukarno. Consciously or not, the Islamic teaching viewed by those framers of Pancasila absorbed into the values of Pancasila. Therefore, it is fair enough that Pancasila and Islam have harmony and conformity, including the concepts of religious harmony and freedom.Â Wacana kerukunan dan kebebasan beragama masih menjadi kajian aktualÂ dan banyak dikaji melalui berbagai pendekatan, diantaranya dalam perspektif sejarah, sosiologi, dan budaya. Di Indonesia, secara normatif,Â praktik kerukunan dan kebebasan beragama mengacu pada nilai agama Islam dan Pancasila sekaligus. Kedua acuan normative tersebut diposisikan sejalan. Bahkan bagi sebagian kalangan Pancasila memiliki ruh ajaran Islam, karena para perumus Pancasila (dan UUD 1945) adalah umat Islam, seperti Muhammad Yamin dan Soekarno. Disadari atau tidak, ajaran Islam yang dipersepsi para perumus Pancasila tersebut meresap kedalam Pancasila. Oleh karena itu, wajar apabila antara Pancasila dan Islam memiliki keselarasan dan kesesuaian, termasuk dalam hal konsep kerukunan dan kebebasan beragama.